Performance and Techno-Economic Analysis of Scaling-up A Single-Chamber Yeast Microbial Fuel Cell as Dissolved Oxygen Biosensor - Marcelinus Christwardana; Linda Aliffia Yoshi (Center of Biomass & Renewable Energy, Diponegoro University, 2020)
The Microbial fuel cells (MFCs) are electrochemical devices that can be utilized as biosensors, specifically Dissolved Oxygen (DO) biosensors. In this research, performance and techno-economic of MFC-based DO biosensors with two sizes, small and large, were evaluated and analysed to determine whether it is more economical to use a small or large reactor. MFC-based DO biosensors were also applied to an irrigation canal. When MFC immersed into distilled water with several variations of DO, the correlation between DO and current density produced equation with R2 values around 0.9989 and 0.9979 for SYMFC and LYMFC, respectively. The power density for SYMFC and LYMFC was 3.48 and 10.89 mW/m2, respectively, in DO 6. Higher power densities are correlated with the electrode surface area, especially the larger cathodic surface area. When applied to the irrigation canal, DO values measured using SYMFC and LYMFC have errors of around 3.39 and 4.42%, respectively, when compared to DO values measured using DO meters. LYMFC requires a capital cost of around 234.22 or 2.57 times higher than SYMFC, although it generates almost similar cost per mW/m2, 21.51 and 26.23 for LYMFC and SYMFC, respectively. The results concluded that yeast MFC -based DO biosensors with smaller sizes can achieve more economical compared to larger sizes.